2018
DOI: 10.1002/oby.22253
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Post‐Oral Actions of Low‐Calorie Sweeteners: A Tale of Contradictions and Controversies

Abstract: Objective: Many scientists and laypeople alike have concerns about low‐calorie sweeteners (LCSs). These concerns stem from both a dissatisfaction with the taste of LCSs and reports that they cause metabolic disruptions (e.g., weight gain, glucose intolerance). Methods: This article provides a critical review of the literature on LCSs from the standpoint of their taste, gastrointestinal, and metabolic effects; biological fate in the body; and impact on ingestion and glucose homeostasis. Results and Conclusions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 123 publications
(152 reference statements)
0
21
0
Order By: Relevance
“…It was observed that non‐caloric sweeteners are fully cross‐adapted by sugars, but sugars are only partially cross‐adapted by non‐caloric sweeteners, indicating the existence of a T1R‐independent receptor site (or sites) that mediates the perception of sugar sweetness. Concerning taste intensity, although non‐caloric sweeteners evoke a sweet taste at lower concentrations than sugars, indicating a higher affinity of non‐caloric sweeteners for T1Rs than that of sugars for T1Rs or SGLTs, artificial sweeteners reportedly have a tendency to elicit a lower maximal sweet taste intensity than sugars in human, 35,36 and to elicit a lower rate of licking in rodents 37 …”
Section: Discussionmentioning
confidence: 99%
“…It was observed that non‐caloric sweeteners are fully cross‐adapted by sugars, but sugars are only partially cross‐adapted by non‐caloric sweeteners, indicating the existence of a T1R‐independent receptor site (or sites) that mediates the perception of sugar sweetness. Concerning taste intensity, although non‐caloric sweeteners evoke a sweet taste at lower concentrations than sugars, indicating a higher affinity of non‐caloric sweeteners for T1Rs than that of sugars for T1Rs or SGLTs, artificial sweeteners reportedly have a tendency to elicit a lower maximal sweet taste intensity than sugars in human, 35,36 and to elicit a lower rate of licking in rodents 37 …”
Section: Discussionmentioning
confidence: 99%
“…Sweetness intensity is associated with liking and reducing sucrose can negatively impact the hedonic appeal of a product and consumer acceptance of reformulated products, thereby limiting the widespread reduction of sucrose to achieve these public health goals. Non-nutritive sweeteners can be used to maintain product sweetness, while reducing the negative health impact of excessive sucrose intake, including increased body weight and risk of type-2 diabetes and cardiovascular diseases [ 6 , 7 , 8 ]. Sweet taste intensity has been shown to be associated with sucrose content of a product, but not with its energy content [ 9 , 10 ] thus creating an opportunity to reduce energy whilst matching sweet taste intensity and liking through the use of lower calorie sweeteners.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic non-nutritive sweeteners like aspartame and sucralose are still the most widely consumed due to their low cost, quality of their sweet taste and calorie-free advantage, although their long-term metabolic impacts are still being investigated [ 8 ]. In addition to reduced sucrose and calories, in recent years there has been a rise in consumer demand for ‘natural’ and clean-label ingredients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent expert stakeholder panel proposed a number of research priorities for LES and health outcomes (11). While that panel did not specifically address issues relating to the execution of research and reporting on LES, others have highlighted issues in experimental design and interpretation that can magnify apparent inconsistencies in the evidence base (12)(13)(14). In this commentary, we highlight specific practices which can be considered as part of guidance to improve the design, reporting and interpretation of research on LES.…”
mentioning
confidence: 99%